A new Mn(II)-based coordination polymer: selective ion-sensing property and treatment activity on temporary osteoporosis of the hip by activating wnt/β-catenin signaling pathway in bone marrow stem cells. (23rd February 2022) - Yuan, Xiao-Qing; Fang, Xiao-Hui; Yang, Jun
ABSTRACT: A new porous 3D coordination polymer (CP), namely [Mn2 (Htpim)2 (odpa)]·8H2 O (1, Htpim = 2, 4, 5-tri(4-pyridyl)-imidazole, odpa = 4, 4′-oxydiphthalate), was successfully synthesized. Furthermore, complex 1 could be applied as a probe displaying good ion sensing property of Cr 3+ ion by fluorescence quenching. For the treatment of the temporary osteoporosis of the hip (TOH), the biological function of the compound was evaluated. Annexin V-FITC/PI assay was performed to measure the bone marrow stem cells' apoptosis after compound treatment. Besides, western blot was utilized to determine the signaling pathway of the wnt/β-catenin activation in bone marrow stem cells.